2023
DOI: 10.3389/fimmu.2023.1264327
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial blockade for cancer immunotherapy: targeting emerging immune checkpoint receptors

Dia Roy,
Cassandra Gilmour,
Sachin Patnaik
et al.

Abstract: The differentiation, survival, and effector function of tumor-specific CD8+ cytotoxic T cells lie at the center of antitumor immunity. Due to the lack of proper costimulation and the abundant immunosuppressive mechanisms, tumor-specific T cells show a lack of persistence and exhausted and dysfunctional phenotypes. Multiple coinhibitory receptors, such as PD-1, CTLA-4, VISTA, TIGIT, TIM-3, and LAG-3, contribute to dysfunctional CTLs and failed antitumor immunity. These coinhibitory receptors are collectively ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 224 publications
0
4
0
Order By: Relevance
“…Previous studies in preclinical models and human cancer tissues have shown that VISTA is highly expressed within the TME, either on tumor-associated myeloid APCs or aberrantly expressed on tumor cells (12)(13)(14)(30)(31)(32). The abundance of VISTA in tumor tissues indicates the potential role of trans-VISTA in driving T cell dysfunction.…”
Section: Lrig1 Inhibits T Cell Proliferation Survival and Effector Fu...mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies in preclinical models and human cancer tissues have shown that VISTA is highly expressed within the TME, either on tumor-associated myeloid APCs or aberrantly expressed on tumor cells (12)(13)(14)(30)(31)(32). The abundance of VISTA in tumor tissues indicates the potential role of trans-VISTA in driving T cell dysfunction.…”
Section: Lrig1 Inhibits T Cell Proliferation Survival and Effector Fu...mentioning
confidence: 98%
“…V domain immunoglobulin suppressor of T cell activation (VISTA)-also known as Dies1, Gi24, PD-1H, or DD1α-is a B7 family immune checkpoint protein and a next-generation immunotherapy target (9)(10)(11)(12)(13)(14). Previous studies have indicated that VISTA inhibits T cell activation by two modes of action: VISTA expressed on antigen-presenting cells (APCs) mediates the "trans" suppression by engaging its cognate receptor on T cells, whereas VISTA expressed on T cells elicits "cis" intrinsic suppression (9,11,15).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of FDA-approved therapies targeting TIM-3, the advancement of novel TIM-3 inhibitors is rapidly evolving in lung cancer. Numerous TIM-3-specific antibodies, such as cobolimab, sabatolimab (MBG453), BMS-986258, AZD7789, INCAGN02390, etc., are under investigation [ 104 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Strategies to tailor inhibitory receptor disruption in tumor-specific cellular products have been proposed to overcome these limitations, but are mainly focused on PD-1- or CTLA-4- disrupted cells tested in short-term anti-tumor responses ( 23 31 ). Here, we selected TIM-3, LAG-3 and 2B4, three inhibitory receptors frequently expressed by T cells in several cancer types and involved in resistance to immunotherapy ( 32 , 33 ), and we exploited the multiplexicity of CRISPR/Cas9 with lentiviral vectors to simultaneously redirect T cell specificity and disrupt genes encoding for TIM-3, LAG-3, or 2B4, within a protocol able to expand long-living early differentiated T SCM ( 34 ). With this approach, we investigated the relative contribution of distinct IR knocked-out in tumor specific cellular products chronically challenged by multiple myeloma cells.…”
Section: Introductionmentioning
confidence: 99%